2020
DOI: 10.1096/fj.202001508r
|View full text |Cite
|
Sign up to set email alerts
|

EBV‐miR‐BART12 accelerates migration and invasion in EBV‐associated cancer cells by targeting tubulin polymerization‐promoting protein 1

Abstract: Epstein-Barr virus (EBV) infection leads to cancers with an epithelial origin, such as nasopharyngeal cancer and gastric cancer, as well as multiple blood cell-based malignant tumors, such as lymphoma. Interestingly, EBV is also the first virus found to carry genes encoding miRNAs. EBV encodes 25 types of pre-miRNAs which are finally processed into 44 mature miRNAs. Most EBV-encoded miRNAs were found to be involved in the occurrence and development of EBV-related tumors. However, the function of EBV-miR-BART12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…As we know, both EBV and human miRNAs play important roles in NPC carcinogenesis and could be drug targets or prognostic biomarkers. The literature review showed that all six miRNAs have been reported to be associated with carcinogenesis in NPC or other cancers (Choi et al, 2013;Liu et al, 2013;Li et al, 2015;Choi and Lee, 2017;Ma et al, 2018;Wu et al, 2020;Jia-Yuan et al, 2020). EBV-encoded miRNA BART12 could promote cell migration and invasion of EBV-associated NPC and gastric cancer by inhibiting TPPP1 mRNA and activating the cellular EMT process (Wu et al, 2020), and miR-BART15-5p could target BRUCE mRNA and TAX1BP1 gene in cancer cells and increase apoptosis and chemosensitivity to 5-FU (Choi et al, 2013;Choi and Lee, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As we know, both EBV and human miRNAs play important roles in NPC carcinogenesis and could be drug targets or prognostic biomarkers. The literature review showed that all six miRNAs have been reported to be associated with carcinogenesis in NPC or other cancers (Choi et al, 2013;Liu et al, 2013;Li et al, 2015;Choi and Lee, 2017;Ma et al, 2018;Wu et al, 2020;Jia-Yuan et al, 2020). EBV-encoded miRNA BART12 could promote cell migration and invasion of EBV-associated NPC and gastric cancer by inhibiting TPPP1 mRNA and activating the cellular EMT process (Wu et al, 2020), and miR-BART15-5p could target BRUCE mRNA and TAX1BP1 gene in cancer cells and increase apoptosis and chemosensitivity to 5-FU (Choi et al, 2013;Choi and Lee, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During EET, tumor cells lose their polarity and tight junctions, and gain the ability to infiltrate and migrate. This process is accompanied by the transition from epithelial marker molecules to endothelial marker molecules, such as decreased expression of tight junction proteins such as E-cadherin and occludin, and increased expression of vimentin, VE-cadherin (adhesion molecule of endothelial cells), fibronectin, vitronectin, and other molecules [106,107]. Among these, E-cadherin is a tight junction protein between epithelial cells, and its expression is significantly downregulated in VM [108].…”
Section: Hypoxia Promotes Vasculogenic Mimicry By Facilitating Epithementioning
confidence: 99%
“…HIF-1 can bind to the hypoxia response element (HRE) on the Twist, Snail, and ZEB2 promoter sequences in the nucleus to play a regulatory role [118][119][120]. Twist protein, a helix-loop-helix transcription factor, belonging to the bHLH transcription factor family, is encoded by the Twist gene located on human chromosome 7p21, and contains two transcription factors, Twist1 and Twist2 [107]. TWIST expression can downregulate the expression of multiple epithelial genes and activate the expression of endothelial genes [106].…”
Section: Hypoxia Promotes Vasculogenic Mimicry By Facilitating Epithementioning
confidence: 99%
“…The ability of single-cell gene expression profiling to identify specific patterns of gene expression allows for the elucidation of mechanisms underlying tumor invasion and metastasis [102][103][104][105] that are critical for preventing the spread of cancer, which considerably complicates treatment (Table 2 (see Additional file 3)).…”
Section: Discovery Of Invasion and Metastasis Mechanismsmentioning
confidence: 99%